2012
DOI: 10.1007/s00198-012-2157-9
|View full text |Cite
|
Sign up to set email alerts
|

Six-year follow-up study of bone mineral density in patients with systemic lupus erythematosus

Abstract: In this 6-year follow-up study, bone loss was remarkably low. A dose-dependent relationship between glucocorticoid use and spinal bone loss was found. In addition, the use of antimalarials and lower 25-hydroxyvitamin D levels at baseline were associated with BMD loss. These findings underline the importance of prevention and treatment of vitamin D deficiency and osteoporosis in SLE, especially in patients using glucocorticoids or antimalarials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
66
1
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 27 publications
10
66
1
5
Order By: Relevance
“…This finding reinforces the deleterious effect of glucocorticoids even in premenopausal SLE women as demonstrated in the minority of the longitudinal studies, which have associated bone loss at lumbar spine with prednisolone use at mean daily doses >7.5 mg [18][19][20]22]. After multivariate analysis, P1NP remained an independent risk factor for BMD loss suggesting that this bone formation marker, by itself, has a great potential in predicting BMD change.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This finding reinforces the deleterious effect of glucocorticoids even in premenopausal SLE women as demonstrated in the minority of the longitudinal studies, which have associated bone loss at lumbar spine with prednisolone use at mean daily doses >7.5 mg [18][19][20]22]. After multivariate analysis, P1NP remained an independent risk factor for BMD loss suggesting that this bone formation marker, by itself, has a great potential in predicting BMD change.…”
Section: Discussionsupporting
confidence: 66%
“…Cross-sectional studies in premenopausal women show an association between lower bone mass and both SLE disease and previous glucocorticoid use [2,[10][11][12][13][14][15][16]. Conversely, the majority of longitudinal studies conclude that bone loss is minimal or not significant in premenopausal SLE patients [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies the prevalence of osteoporosis in GC treated patients with SLE ranged from 1.4 to 68% (34,35). Two recent studies have demonstrated that bone loss occurs mainly in SLE patients treated with at least 7.5 mg/ day prednisone, while treatment with lower doses of prednisone is not associated with bone loss (36,37). The frequency of osteoporosis in patients with PMR in previous studies ranges between 14.9 and 85%.…”
Section: N Discussion and Conclusionmentioning
confidence: 99%
“…Based on etiology, OP is divided into 3 types: primary, secondary and idiopathic OP. Secondary OP is induced by some drugs and diseases, such as glucocorticoids and lupus erythematosus [3,4].…”
Section: Introductionmentioning
confidence: 99%